The improved Trajectory-mapped Ozonesonde dataset for the Stratosphere and Troposphere (TOST): update, validation and applications - Z. Zang; J. Liu; D. Tarasick; O. Moeini; J. Bian; J. Zhang; A. M. Thompson; A. M. Thompson; R. Van Malderen; H. G. J. Smit; R. M. Stauffer; B. J. Johnson; et al. (Atmospheric Chemistry and Physics)
A global-scale horizontally and vertically resolved ozone climatology provides detailed insights into ozone variability. Here, the seasonal, annual and decadal monthly Trajectory-mapped Ozonesonde dataset for the Stratosphere and Troposphere (TOST) ozone climatology is improved and updated over 1970–2021. TOST is gridded at 5°×5°×1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="ad588ae18150d1e1e96560241601e3b7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-13889-2024-ie00001.svg" width="52pt" height="10pt" src="acp-24-13889-2024-ie00001.png"/></svg:svg> km (latitude, longitude and altitude) from the surface to 26 km by the geometric coordinate and from the surface to 20 hPa at 26 pressure levels by the pressure coordinate, with the most recent ozonesonde data re-evaluated following the ASOPOS-2 guidelines (Smit and Thompson, 2021). Comparison between ozonesonde and trajectory-derived ozone shows good agreement for each decade, altitude and station, with relative differences (RDs) of 2 %–4 % in the troposphere and 0.5 % in the stratosphere. TOST also aligns well with aircraft, the Satellite Aerosol and Gas Experiment (SAGE) and the Microwave Limb Sounder (MLS) datasets. The updated TOST improves data coverage in all latitude bands and altitudes and reduces RD by 14 %–17 % compared to the previous version, taking advances in trajectory simulations and twice as many ozonesonde profiles. Higher uncertainties in TOST are where data are sparse, i.e., southern high latitudes, tropics and pre-1980s, and where variability is high, i.e., at the surface and upper troposphere–lower stratosphere (UTLS). Caution should therefore be taken when using TOST in these spaces and times. TOST captures global ozone distributions and temporal variations, showing an overall non-significant change in lower stratospheric ozone after 1998. TOST offers users a dataset with a long record, global coverage and high vertical resolution.